Clinical profile of patients admitted with pericardial effusion in Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Neupane, Keshab Raj; Simkhada, Rabindra; Manandhar, Reeju; Kansakar, Subodh; Yadav, Dharmanath; Kadel, Arun; Kharel, Sushant; Thapa, Aashika; Shrestha, Prinsa; Sahi, Ravi (Nepalese Heart Journal, 2023)
Background and Aims: Pericardial effusion is a common finding in every day clinical practice. It is caused by a range of local and systemic disorders, many of which could be idiopathic. Pericardial effusions can be acute or chronic. The etiology of pericardial effusion varies in different parts of the world and is related to the relative prevalence of different diseases. Methods: This is a retrospective study where data from all the cases admitted with pericardial effusion in the SGNHC from January 2021 to December 2022 were included. Altogether 218 cases diagnosed with pericardial effusion established by Echocardiograpy were included. Evaluation for the cause of pericardial effusion was done. Iatrogenic (cardiac surgery, catheterization) and post-traumatic cases and age <15 years were excluded. Demographic profile, common causes, the presentation and the clinical outcome of the patients were documented. Results: Majority of patients were aged between 56-75 years. Most common etiology of pericardial effusion was tuberculosis (56%) followed by heart failure (11%), Hypothyroidism (6.4%) and malignancy (5.6%). Tachycardia was the most common ECG finding in 152 (69.7%) followed by Low voltage ECG in 96 (44%). The most common clinical feature was breathlessness in 85% followed by tachycardia in 56% of the patient. Conclusion: Tuberculosis, Heart Failure and Hypothyroidism were the common causes of Pericardial effusion with male predominance. Breathlessness was the most common presenting symptom.